FINANCIAL FITNESS OF SELECTED PHARMACEUTICALS COMPANIES OF BANGLADESH: A COMPARATIVE ASSESSMENT - Akter, Sultana (American Economic & Social Review, 2021)
To understand the financial condition of a firm, it is mandated to evaluate the financial fitness of a firm, whether manufacturing, trading and service rendering etc. The main purpose of this research is to measure the financial fitness of leading pharmaceutical industries and listed on the stock exchange in Bangladesh. This study employs a sample of seven companies from pharmaceutical industries in Bangladesh where Altman’s Z-score model is used to assess the financial fitness of those companies by the prediction of whether they will go into bankruptcy within the next two years. By applying the model, it is revealed that SQUARE Pharmaceuticals Ltd, Renata Limited and IBN SINA Pharmaceutical Limited are in a very good position with higher Z-Score. Beacon Pharmaceuticals Limited and Ambee Pharmaceuticals Limited are heading toward good scores. But ACI Limited and Beximco Pharmaceuticals Limited are financially unhealthy and there is a possibility of going into bankruptcy in the near future. The finding of the study suggested the main reason for such a situation is that the performance of companies is differed by declining market value of shares, falling total asset turnover, inadequate proportion of EBIT to total assets and insufficient liquid assets etc. JEL Classification Codes: G33, G53, M10.